PELATIHAN PERHITUNGAN DAN PENCATATAN ASET TETAP BAGI SISWA/I SMA PROVIDENTIA - Elfenso, Parcella Glatia; Viriany (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Teaching activities in the education represent a manifestation of a student-centered learning approach. The independent campus learning model presents challenges and opportunities for the development of innovation, creativity, personality, and addressing the needs of students. This system also aims to cultivate independent skills in seeking and acquiring knowledge through real experiences and field dynamics, including problem-solving, social interaction, collaboration, and self-management.The goal of the teaching assistance program in the Education unit is to provide students with the opportunity to learn and develop themselves while assisting schools in delivering optimal education services to all high school students. This program also aims to sharpen students' thinking skills in solving the problems they encounter. Teaching Assistant Activities will be organized specifically for students of SMA Providentia, located at Jl. Kedoya Raya No. 35, RT.14/RW.7, Kedoya Utara, West Jakarta. The implementation of this program will involve the direct delivery of information to the participants of the teaching, who are the students of SMA Providentia, in the form of face-to-face meetings. The program's duration will run from August 2023 to November 2023. This will be achieved by applying the knowledge imparted by lecturers from Tarumanagara University to the students of SMA Providentia. Teaching Assistant Activities will commence with an initial meeting between the school and Tarumanagara University to identify the school's needs and interests related to this collaboration. We have concluded that the theme we have chosen is